2010
DOI: 10.1124/dmd.110.034637
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Liquid Chromatography-Tandem Mass Spectrometry Method to Determine Relative Plasma Exposures of Drug Metabolites across Species for Metabolite Safety Assessments

Abstract: ABSTRACT:Recent regulatory guidance suggests that metabolites identified in human plasma should be present at equal or greater levels in one of the animal species used in safety assessments. In this report, a high-performance liquid chromatography-tandem mass spectrometry method is described whereby quantitative comparisons of exposures to metabolites between species can be obtained in the absence of authentic standards of the metabolites, calibration curves, and other attributes of standard bioanalytical meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 25 publications
(23 reference statements)
2
63
0
Order By: Relevance
“…A simple HPLC-MS/MS method was presented whereby quantitative comparisons of exposures to metabolites between animal and human can be obtained in the absence of authentic standards of the metabolites, calibration curves, and other attributes of standard bioanalytical methods (10,13). A statistical analysis showed that if the experimentally determined, animal-to-human MS response ratio is ≥2.0 then the actual exposure ratio is unity or greater (p<0.01).…”
Section: A Simple Lc/ms/ms Methods For Evaluating Mist Coveragementioning
confidence: 99%
See 2 more Smart Citations
“…A simple HPLC-MS/MS method was presented whereby quantitative comparisons of exposures to metabolites between animal and human can be obtained in the absence of authentic standards of the metabolites, calibration curves, and other attributes of standard bioanalytical methods (10,13). A statistical analysis showed that if the experimentally determined, animal-to-human MS response ratio is ≥2.0 then the actual exposure ratio is unity or greater (p<0.01).…”
Section: A Simple Lc/ms/ms Methods For Evaluating Mist Coveragementioning
confidence: 99%
“…The currently available techniques may be integrated to reliably find and structurally identify the metabolites from the plasma and urine samples that are already collected in typical phase I clinical trials. And semiquantitation of metabolites using liquid chromatography (LC)-UV, LC/MS/MS peak area ratio comparison (10,11,13), radiolabeled calibrant (5-7), and quantitative NMR standards (8,9,14) can be employed to compare the exposures to the metabolites in animals to humans. This allows a sponsor to comply with regulatory expectations for metabolite safety assessment without the need to wait for the conventional 14 C-ADME studies that are usually conducted in phases II or III.…”
Section: Early Assessment Of Mist Liability Of a Clinical Drug Candidmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these approaches include mixed matrix LC-MS/MS peak area comparisons across species [13], NMR-based techniques [14,15], and bioanalytical methods with radiocalibrants [16]. LC-MS peak area comparisons between animals and humans are routinely used by some sponsors to demonstrate that metabolite concentrations in animals exceed plasma concentrations in humans.…”
Section: Introductionmentioning
confidence: 99%
“…One approach adjusts the LC-MS signal of a metabolite with its MS signal response factor relative to the parent drug, as determined by correlating the MS and radiochromatographic signal responses in radiolabeled metabolite studies (Yu et al, 2007;Yi and Luffer-Atlas, 2010). Another method more efficient in time and resources is the direct comparison of the LC-MS signal of metabolite samples between different species after adding blank plasma of different species to each other to eliminate potential differences in sample matrix effect (Gao et al, 2010;Ma et al, 2010, Haglund et al, 2014.…”
Section: Introductionmentioning
confidence: 99%